Ecophysiological Traits Associated with Drought in Mediterranean Tree Seedlings: Individual Responses versus Interspecific Trends in Eleven Species - Valladares, F.; Sánchez-Gómez, D. (Plant Biology, 2006)
Abstract: Species differ regarding their drought tolerance and individuals of a given species can modify their morphology and physiology in response to drought. However, since evolutionary and ecological selective pressures differ, individual and interspecific responses to drought might not match. We determined summer survival and a number of ecophysiological variables in two factorial experiments with seedlings of eleven tree species present in Mediterranean ecosystems, grown under slowly imposed water stress and control conditions. Plants experiencing drought exhibited reduced growth, low specific leaf area, chlorophyll content, and photosynthetic rate when compared to the controls, and species-specific drought tolerance was associated with an analogous set of trait values. However, while species with high leaf area ratio and shoot-root ratio exhibited greater drought tolerance, drought induced the reversed response within species. Contrary to expectations, water use efficiency was lower in drought-tolerant species and decreased in water-stressed individuals compared to the control plants. There was a distinctive phylogenetic signal in the functional grouping of species, with oaks, pines, and other genera being clearly different from each other in their drought tolerance and in their functional responses to drought. However, all relationships between ecophysiological variables and drought tolerance were significant after accounting for phylogenetic effects, with the exception of the relationship between drought tolerance and photochemical efficiency. Our results show that drought tolerance is not achieved by a single combination of trait values, and that even though evolutionary processes and individual responses tend to render similar results in terms of functional traits associated with drought, they do not necessarily match.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Drought tolerance; functional traits; Mediterranean plants; phylogeny; water use efficiency; woody seedlings

Ecophysiological Traits Associated with Drought in Mediterranean Tree Seedlings: Individual Responses versus Interspecific Trends in Eleven Species - Valladares, F; Sánchez-Gómez, D (Plant Biology, 2006)
Abstract: Species differ regarding their drought tolerance and individuals of a given species can modify their morphology and physiology in response to drought. However, since evolutionary and ecological selective pressures differ, individual and interspecific responses to drought might not match. We determined summer survival and a number of ecophysiological variables in two factorial experiments with seedlings of eleven tree species present in Mediterranean ecosystems, grown under slowly imposed water stress and control conditions. Plants experiencing drought exhibited reduced growth, low specific leaf area, chlorophyll content, and photosynthetic rate when compared to the controls, and species-specific drought tolerance was associated with an analogous set of trait values. However, while species with high leaf area ratio and shoot-root ratio exhibited greater drought tolerance, drought induced the reversed response within species. Contrary to expectations, water use efficiency was lower in drought-tolerant species and decreased in water-stressed individuals compared to the control plants. There was a distinctive phylogenetic signal in the functional grouping of species, with oaks, pines, and other genera being clearly different from each other in their drought tolerance and in their functional responses to drought. However, all relationships between ecophysiological variables and drought tolerance were significant after accounting for phylogenetic effects, with the exception of the relationship between drought tolerance and photochemical efficiency. Our results show that drought tolerance is not achieved by a single combination of trait values, and that even though evolutionary processes and individual responses tend to render similar results in terms of functional traits associated with drought, they do not necessarily match.
Keywords: Drought tolerance; functional traits; Mediterranean plants; phylogeny; water use efficiency; woody seedlings

The effect of drought on gas exchange and water potential in leaves of seven Mediterranean woody species - Gucci, R; Massai, R; Casano, S; Gravano, E; Lucchesini, M (IMPACTS OF GLOBAL CHANGE ON TREE PHYSIOLOGY AND FOREST ECOSYSTEMS, 1998)
The water relations and gas exchange parameters of Arbutus unedo, Cistus monspeliensis, Erica arborea, Myrtus communis, Phillyrea latifolia, Pistacia lentiscus, and Quercus ilex growing in the shrubland vegetation at the Parco Naturale della Maremma (Italy), were studied over two consecutive years. At high leaf water potentials, photosynthetic rates and stomatal conductance were relatively low in all species but C. monspeliensis. Stomatal conductance remained relatively high in C. monspeliensis leaves as soil moisture was depleted, whereas A. unedo, E. arborea, M. communis, and P. lentiscus were more conservative in water use. P. latifolia and Q. ilex showed a drought-tolerant behaviour.
Keywords: Drought tolerance; leaf water potential; Phenology; Stomatal conductance

Variability in seedling water status during drought within a Quercus ilex subsp. ballota population, and its relation to seedling morphology - Leiva, María José; Fernández-Alés, Rocı́o (Forest Ecology and Management, 1998)
Differences in morphology, growth and plant water status during drought were studied in greenhouse-grown Quercus ilex subsp. ballota seedlings produced by different mother trees occurring in a savannah-like forest (locally named dehesa) in southern Spain. There were signi®cant differences among mother trees in the biomass of their seeds (mother tree level accounted for 62% of total variance in this trait), in the percentage of seedlings that emerged and in the time of shoot emergence. The progeny that had high emergence rates (80±90%) also had short emergence times while the opposite was true for the progeny that had low (43%) and intermediate (70%) emergence rates. Acorn biomass covaried signi®cantly with seedling total biomass and with the biomass of different parts of the seedlings, but not with the partitioning of biomass among roots and shoots (root/shoot ratio) nor to morphological seedling traits such as shoot height, total leaf area, average leaf size, speci®c leaf area (SLA) and leaf number. All these traits varied signi®cantly among the seedlings produced by different mother trees. The conductance to water vapour (glw) of the foliage of the seedlings also varied signi®cantly among mother trees and was dependent on the root/shoot ratio as on the total leaf area of the seedlings, but not on the total seedling biomass. One of the six trees that were studied produced seedlings which had a signi®cantly higher root/shoot ratio, smaller leaf area, smaller leaves, higher speci®c leaf area and shorter stems than the seedlings produced by any other tree. In addition, the former set of seedlings had signi®cantly higher glw 15 and 30 days after drought, and higher leaf water content at the end of the experiment than the other seedlings. We discuss the value of using single seedling traits related to drought tolerance such as root/shoot ratio and leaf area in the framework of the restoration of savannah-like oak forest in the Mediterranean areas. We also discuss the functional implications of the diversity of genotypes within the oak populations in the framework of the global climate change
Keywords: Drought tolerance; Holm oak; root/shoot ratio; savannah-like forest; seedling biomass

Planta of resurrection plants to desiccation and rehydration - Schwab, K. B.; Schreiber, U.; Heber, U. (1989)
Using non-invasive techniques (CO2 gas exchange, light scattering, light absorption, chloro- phyll fluorescence, chlorophyll luminescence), we have analysed the response of respiration and pho- tosynthesis to dehydration and rehydration of leaves of the resurrection plants Craterostigma plantagineum Hochst., Ramonda mykoni Reichb. and Ceterach officinarum Lam. et DC. and of the drought-sensitive mesophyte spinach (Spinacia oleracea L.). The following observations were made: (i) The rate of water loss during wilting of detached leaves of drought-tolerant resurrection plants was similar to that for leaves of the sensitive mesophyte, spinach. Leaves of Mediterranean xerophytes lost water much more slowly. (ii) Below a residual water content of about 20%, leaves of spinach did not recover turgor on rewatering, whereas leaves of the resurrection plants did. (iii) Respiration was less sensitive to the loss of water during wilting in the resurrection plants than in spinach. (iv) The sensitivity of photosynthesis to dehydration was similar in spinach and the resur- rection plants. Up to a water loss of 50% from the leaves, photosynthesis was limited by stomatal closure, not by inhibition of reactions of the photo- synthetic apparatus. Photosynthesis was inhibited and stomates reopened when loss of water became excessive. (v) After the leaves had lost 80% of their water or more, the light-dependent reactions of photosynthetic membranes were further inhibited by rewatering in spinach; they recovered in the resurrection plants. (vi) In desiccated leaves of the resurrection plants, slow rehydration reactivated mitochondrial gas exchange faster than photosyn- thetic membrane reactions. Photosynthetic carbon assimilation recovered only slowly.
Keywords: Carbon dioxide (gas exchange); Chlorophyll (fluorescence - luminescence); Drought tolerance; Light scattering (thylakoids); Resurrection plants; water stress